MERGERS AND ACQUISITIONS VALUATION FOR THE ACQUISITION OF PT LIPPO KARAWACI TBK BY PT BUMI SERPONG DAMAI TBK - Dwi Wuryantadi; Jerry Heikal (Cerdika: Jurnal Ilmiah Indonesia, 2023)
The purpose of this study is to determine mergers and acquisitions valuation for the acquisition One of the strategic objectives aimed at enhancing performance is product diversification. By acquiring PT Lipo Karawaci Tbk (LPKR), PT Bumi Serpong Damai Tbk (BSDE) aspires to expand its product portfolio by incorporating the existing offerings of LPKR. The method use quantitative methodology, characterized by the collection of numerical data and subsequent analysis by statistical tools. The primary objective of this study is to quantitatively quantify and provide an objective analysis of various eventsThe successful execution of this corporate activity necessitates meticulous calculation to effectively enhance the performance of the purchasing company, hence accomplishing its primary objective. One of the research objectives is to ascertain the valuation of PT Lippo Karawaci Tbk (LPKR) as a firm. The free cash flow method, often known as FCFF, is a viable approach for conducting assessments within the context of corporations. The aforementioned are financial concepts and measures employed for the purpose of quantifying the quantity of cash created by a corporate entity. In order to ascertain the post-acquisition predictions of the company for the subsequent five-year period (2023-2027), an analysis of the financial report data of both entities from 2020 to 2027 is required.